Constitutive Investigation on Viscoelasticity of PolyVinyl Butyral: Experiments Based on Dynamic Mechanical Analysis Method - Bohan Liu; Jun Xu; Yibing Li (Advances in Materials Science and Engineering)
PolyVinyl Butyral (PVB) film is now widely used in automotive industry and architectures serving as the protective interlayer. The dynamic modulus of PVB is measured through systematic experiments based on Dynamic Mechanical Analysis (DMA) method at various temperatures, heating rates, and vibration frequencies. Further, viscoelasticity of PVB influenced by time and temperature is systematically studied. Fitted empirical formulas describing the relationship between glass transition temperature and frequency, as well as the heating rate of PVB, are established. The master curve of PVB at 293 K is suggested based on the experiment data as to express the dynamic modulus variation at various frequencies in a wider range. Constitutive behavior of PVB is then analyzed based on Generalized Maxwell (GM) model and Fractional Derivative (FD) model, respectively. It is shown that PVB has higher efficiency of energy dissipation in its high energy absorption state, while both fifth-order GM model and FD model can characterize the viscoelasticity of PVB at glassy transition area. Results may offer useful fundamental experimental data and important constitutive characteristics of PVB and shed lights on further studies on viscoelasticity behavior of PVB and energy mitigation ability of laminated glass.